Cavell’s Shakespeare, or the Insufficiency of Tragedy for Modernity - Jukić, Tatjana (Bollettino Filosofico, 2017)
Stanley Cavell’s philosophical interest in Shakespeare is so consistent that Shakespeare appears to have pre-organized, for Cavell, the intellectual situation from which to launch the ideation of modernity. I propose to discuss Cavell with a view to similar constellations in Walter Benjamin and Carl Schmitt, but careful of the fact that, unlike Schmitt or Benjamin, Cavell does not privilege Hamlet as a text to which Shakespeare appears reducible. Instead, Cavell’s Shakespeare is collective and paratactic, with the implication that tragedy, taken in isolation (even as it morphs into mourning play), fails to capture the truth of modernity. What emerges in Cavell is a Shakespeare whose tragedy works from within a Lockean social contract with other genres - condition crucial to Cavell’s philosophical concerns.